2014
DOI: 10.1021/ol501254h
|View full text |Cite
|
Sign up to set email alerts
|

Non-Precious Metals Catalyze Formal [4 + 2] Cycloaddition Reactions of 1,2-Diazines and Siloxyalkynes under Ambient Conditions

Abstract: Copper(I) and nickel(0) complexes catalyze the formal [4 + 2] cycloaddition reactions of 1,2-diazines and siloxyalkynes, a reaction hitherto best catalyzed by silver salts. These catalysts based on earth abundant metals are not only competent, but the copper catalyst, in particular, promotes cycloadditions of pyrido[2,3-d]pyridazine and pyrido[3,4-d]pyridazine, enabling a new synthesis of quinoline and isoquinoline derivatives, as well as the formal [2 + 2] cycloaddition reaction of cyclohexenone with a siloxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 63 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…), which provided ready access to siloxy naphthalenes 54 (Scheme 23). 66 In a Au(I)-catalysed [4+2] cyclization of isoquinoline N-oxides and siloxy alkynes to naphthols, pyridine N-oxides were unreactive. However, thus far, the reported IEDDA reactions of azadienes are nearly all thermal processes and require high temperatures.…”
Section: Cycloaddition and Cyclizationmentioning
confidence: 99%
“…), which provided ready access to siloxy naphthalenes 54 (Scheme 23). 66 In a Au(I)-catalysed [4+2] cyclization of isoquinoline N-oxides and siloxy alkynes to naphthols, pyridine N-oxides were unreactive. However, thus far, the reported IEDDA reactions of azadienes are nearly all thermal processes and require high temperatures.…”
Section: Cycloaddition and Cyclizationmentioning
confidence: 99%
“…In order to understand the preferred coordination of Ag(I) bipyridine to the reaction partners, two possible complexes of silver with phthalazine and siloxy alkyne were modeled (Figure ). It has been reported that Ag(I) salts, especially when coordinated with bidendate N‐donor ligands, such as 2,2‐bipyridine, catalyze the desired cycloadditon to yield silyl‐protected 2‐napthol . 1,2‐diazines show similarity with bipyridines due to their potential for bidentate chelation.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Rawal et al. have extended their research with the use of copper(I) and nickel(0) complex catalysts, which are isoelectronic with Ag(I) . It was expected that copper(I) and nickel(0) complexes behave differently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,2528 Although there are notable successes, including Wegner’s diboraanthracene 26 for use with phthalazines, Rawal’s Ag(I)-promoted reactions of silyloxy alkynes with phthalazines, 27 and our own use of pressure-promoted reactions, 28 these efforts have been largely unsuccessful in providing a general solution. Typically, additives preferentially lead to consumption of the electron-rich dienophile without productive activation of the electron-deficient heterocyclic azadienes.…”
mentioning
confidence: 99%